PHASE EQUILIBRIA IN ROCKS OF THE PALEOPROTEROZOIC BANDED IRON FORMATION (BIF) OF THE LEBEDINSKOE DEPOSIT, KURSK MAGNETIC ANOMALY, AND THE PETROGENESIS OF BIF WITH ALKALI AMPHIBOLES - Savko K.A. (My University, 2006)
BIF with alkali amphibole at the Lebedinskoe iron deposits, the largest in Russia, were metamorphosed at 550°C and 2–3 kbar and contain ferriwinchite, riebeckite, actinolite, grunerite, and aegirine-augite. All reaction textures observed in the rocks were produced during the prograde metamorphic stage and represent the following succession of mineral replacements: Gru → Rbk, Act → Win → Rbk. Data obtained on the textural relations and compositional variations of Ca, Ca-Na, and Na Al-free amphiboles point to the complete miscibility in the actinolite-ferriwinchite and ferriwinchite-riebeckite isomorphic series. Riebeckite is formed in BIF during the prograde metamorphic stage, with the participation of a fluid insignificantly enriched in Na+ and at increasing oxygen fugacity. The critical factors controlling the development of alkali amphiboles and Ca-Na pyroxenes in carbonate-bearing BIF is the oxygen activity and the presence of at least low concentrations of Na+ ions in the fluid. The minerals contain Fe3+, and all reactions producing them are oxidation reactions. The origin of riebeckite late in the course of the mineral-forming process is caused by the Ca2+Mg2+ → Na+Fe3+ heterovalent isomorphic replacement in calcic and calcic-sodic amphiboles and by the oxidation of grunerite in the presence of a fluid enriched in Na ions.
Keywords: Paleoproterozoic; Precambrian::Proterozoic::Paleoproterozoic; Докембрий::Протерозой::Палеопротерозойская